2002
DOI: 10.1080/03098770220129433
|View full text |Cite
|
Sign up to set email alerts
|

Can we Make Maths Count at HE?

Abstract: The Dearing Report highlighted the need for HE programmes to enhance students' basic skills, and one of these is numeracy skill. There is a history of low con dence and negative attitudes to learning about numbers and 'maths anxiety' in undergraduates which means that delivering 'numerate graduates' may be something of a challenge to HE institutions. This college surveyed attitudes to numeracy and learning about numbers in all rst-year students (over 1000 students). Over 40% of students returned their question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Shepherd (2006) reported the results of a survey of university admissions tutors which concluded that 'undergraduates were entering university less numerate, literate and knowledgeable than ever before' (p. 1). A survey of 466 students completed by Mackenzie (2002) found that less than 3% of the sample had studied mathematics post-GCSE level, so that upon entering university the students had not practised their numeracy skills for at least two years. The possibility arises, therefore, that employers might increasingly be more concerned with ensuring that graduate recruits from vocational degrees have attained basic levels of numeracy and literacy than with requiring that newcomers have completed work placements.…”
Section: Changing Priorities Among Graduate Recruitersmentioning
confidence: 99%
“…Shepherd (2006) reported the results of a survey of university admissions tutors which concluded that 'undergraduates were entering university less numerate, literate and knowledgeable than ever before' (p. 1). A survey of 466 students completed by Mackenzie (2002) found that less than 3% of the sample had studied mathematics post-GCSE level, so that upon entering university the students had not practised their numeracy skills for at least two years. The possibility arises, therefore, that employers might increasingly be more concerned with ensuring that graduate recruits from vocational degrees have attained basic levels of numeracy and literacy than with requiring that newcomers have completed work placements.…”
Section: Changing Priorities Among Graduate Recruitersmentioning
confidence: 99%
“…However, instruction often fails to achieve these goals. This study shows that high engagement in mathematical problem solving, inquiry, and collaboration can offer students a path to these desired tools, skills, and dispositions that are valuable well beyond college classrooms and that also help to achieve desired societal goals such as enhancing citizens' mathematical skills and increasing the number of students pursuing mathematical fields (MacKenzie, 2002;Manigault, 1997). We need to promote the kind of learning environments and instructional practices that will increase all students' opportunities for transformative learning and personal empowerment.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Evans (1999) believes that affect has a strong influence on the ability of students to transfer mathematical skills from one context to another, and argues that this has been largely ignored in accounts of mathematical thinking. Researchers working with adult students report observing high levels of mathematics anxiety (Mackenzie 2002, Perry 2004 and express concerns that when this is associated with poor preparedness, poor mathematical proficiency can develop and be a barrier to further education experiences (Benn and Burton 1993, Benn 1997, O'Donoghue 2000.…”
Section: I T E R a C Y And N U M E R A C Y S T U D I E Smentioning
confidence: 99%
“…Moreover, many commencing students are also reported to have high levels of mathematics anxiety (Mackenzie 2002, Perry 2004. This research has been reinforced over the years by the authors' work in the tertiary context for bridging and undergraduate students.…”
Section: I T E R a C Y And N U M E R A C Y S T U D I E Smentioning
confidence: 99%